The Impact of Digitalization on Women's Employment Participation in Indonesia: A Binary Logistic Regression Analysis - Tevina Carisa Herdinanda; Happy Febrina Hariyani (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Women's employment in Indonesia has shown a substantial increase in recent years.Women's participation in the workforce in Indonesia continues to grow, although there is stilla significant gap compared to men. This is driven by various factors such as digitalization,increased access to education, and policies that support women's involvement in the world ofwork. This study aims to identify and analyze the factors that most affect women's participationin the world of work in Indonesia. Using secondary data from the 2023 National Labor ForceSurvey (Sakernas) with individual observations, the publication of BPS Economic Growth, thewebsite of the Indonesian Digital Society Index, was analyzed using binary logistic regression.The results of the study show that education, work experience, regional classification, andeconomic growth have a significant positive effect on working women while marital status, jobtraining, and the Indonesian Digital Society Index have a significant negative effect on workingwomen. This research shows the importance of a holistic approach to women's empowermentin the world of work, which includes increasing access to education and training, creating asupportive work environment, and utilizing technology to open up wider job opportunities forIndonesian women.